2020
DOI: 10.3389/fncel.2020.571175
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Ethanol on Hippocampal Spatial Representation and Offline Reactivation

Abstract: Acute alcohol exposure impairs hippocampus-dependent spatial memory. However, there is little evidence for the effects of ethanol on the spike patterns of hippocampal cell populations. Here, we examined how the spatial firing patterns of place cells, neurons that encode specific locations, were altered in rats that were intraperitoneally injected with 1.5 g/kg ethanol. Ethanol administration partly reduced or abolished place-selective spiking of a subset of place cells during running periods in a spatial task,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It is necessary for acquiring spatial information to have an intact hippocampus [ 20 ]. HE staining showed that compared with the control group, the model group showed the disordered arrangement of hippocampal neurons and infiltration of inflammatory cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary for acquiring spatial information to have an intact hippocampus [ 20 ]. HE staining showed that compared with the control group, the model group showed the disordered arrangement of hippocampal neurons and infiltration of inflammatory cells.…”
Section: Resultsmentioning
confidence: 99%
“…In a prior experiment conducted by Miyake et al, the effect of acute EtOH administration on the spike patterns of hippocampal cell populations was analysed. The results from their study suggested that EtOH does not significantly alter the SWRs frequency in the hippocampal region (Miyake et al, 2020). While these studies provide valuable insights into the effects of EtOH exposure on SWRs waveforms, further investigations are warranted to fully elucidate the complex relationship between chronic alcohol use and SWRs.…”
Section: Role Of Ripples On Memory Consolidationmentioning
confidence: 99%
“…To the best of the author's knowledge, the evaluation of SWRs in association with memory impairment induced by alcohol administration has been limited to a small number of articles. Specifically, one study examined the response to acute alcohol administration in adult rats (Miyake et al, 2020), while another study investigated the effects of prenatal alcohol exposure on SWR activity (Harvey et al, 2021). The study of the effect of alcohol on SWRs as a memory consolidation biomarker may provide an opportunity for new forms of management to restore and improve cognitive impairment in alcoholism.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of acute ethanol (EtOH) on learning and memory have been investigated in human and rodent students, and memory deficits are usually reported (Lister et al , 1987; Silvers et al , 2003; Matthews and Silvers, 2004; Zorumski et al , 2014; Miyake et al , 2020). Nevertheless, these effects are dependent on several factors such as behavioral task, dose, acquisition/retrieval interval, age, sex, and estrogen levels (Matthews et al, 1995; 1999; Kameda et al , 2007; Broadwater and Spear, 2013; Boissoneault et al , 2014; Hoffman et al , 2015; Hunt and Barnet, 2016; Lewis et al , 2019; Sircar, 2019).…”
Section: Introductionmentioning
confidence: 99%